Advancements in Nanostructured Membranes for Gas Separation: A Comprehensive Review - Shweta Tomar (International Journal of Membranes, 2024)
Gas separation is vital in petrochemical, pharmaceutical, and environmental industries, yet traditional methods like distillation and cryogenic separation are energy-intensive and inefficient. Nanostructured membranes present a promising alternative, utilizing nanomaterials such as titanium dioxide, silica, carbon nanotubes, zeolite, and metal-organic frameworks to enhance separation efficiency and selectivity while reducing energy consumption. These membranes fall into various categories: polymeric nanostructured membranes, including mixed matrix and thin-film composites; inorganic membranes, such as those made from ceramics or carbon; hybrid membranes combining organic and inorganic elements; bio-inspired membranes that mimic natural processes; and advanced membranes utilizing precise nanoscale engineering.Fabrication techniques like template-assisted methods, layer-by-layer assembly, electrospinning, and self-assembly enable tailored membrane properties. Performance evaluation of these membranes focuses on selectivity, permeability, stability, and scalability. Applications are diverse, ranging from natural gas purification and hydrogen production to carbon dioxide capture and air separation, providing energy-efficient and cost-effective solutions. Challenges such as membrane fouling, scalability, and cost-effectiveness remain, necessitating further research into novel materials, optimized fabrication processes, and integration with other technologies. In order to improve gas separation systems' sustainability and efficiency and open the door for wider industrial usage, these problems must be resolved.
Keywords: Advanced Membranes; Gas Separation; Inorganic Membranes; Nanostructured Membranes; Polymeric Membranes